(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The adoption of digital payment solutions has significantly impacted small businesses in Nagpur. This paper examines the challenges and opportunities of these systems, focusing on the impact on market reach, operational efficiency, customer experience, and government support. Key challenges include technological barriers, financial constraints, security concerns, regulatory issues, and customer resistance. However, opportunities include enhanced market reach, operational efficiency, and improved customer experience. The study concludes with recommendations for infrastructure development, financial support, security enhancements, customer education, and policy reforms to facilitate widespread adoption of digital payment solutions. This research provides valuable insights into the digital payment landscape for small businesses, laying the groundwork for further exploration and action in this evolving field.